High flux, positively charged loose nanofiltration membrane by blending with poly (ionic liquid) brushes grafted silica spheres - Yu, L.; Zhang, Y.; Wang, Y.; Zhang, H.; Liu, Jian (Elsevier BV, 2015)
© 2015 Elsevier B.V. Silica spheres modified by poly (ionic liquid) brushes, a novel positively charged nanomaterial is prepared by atom transfer radical polymerization (ATRP). A high flux positively charged loose nanofiltration membrane is fabricated via "blending-phase inversion" method. The morphology structures, hydrophilicity, thermal and mechanical properties, permeation performance of these membranes are investigated in detail. The results reveal that the hybrid membranes have enhanced surface hydrophilicity, water permeability, thermal stability, and mechanical properties. Characterization of membrane separation properties shows that the hybrid membranes possess higher salt permeability and relatively higher rejection for reactive dyes, which may open opportunities for the recycling of reactive dyes wastewater. Moreover, such hybrid membranes have an outstanding operational stability and salts concentration showed little effect on the separation properties.